Tree species have a greater influence on species composition of the herb layer than soil texture on a forested post‐mining area. (5th January 2021) - Rawlik, Mateusz; Kasprowicz, Marek; Jagodziński, Andrzej M.; Kaźmierowski, Cezary; Łukowiak, Remigiusz; Grzebisz, Witold
Abstract: Trees are promoters of forest ecosystems and tree species differ in their manners of shaping the habitat conditions on reclaimed areas. We compared effects of pure forest stands of Alnus glutinosa, Betula pendula, and Pinus sylvestris (age 20–31 years) planted on sandy, loamy sand, sandy loam, and loam soils, on chemical properties of the soil and vascular plants species composition of the herb layer. Studied properties were assessed in pairs of plots located less than 50 m apart, that differed in species composition of the canopy but were characterized by similar abiotic conditions. Forest stands of A. glutinosa were distinguished by a higher SOC content in soil (2.3% vs. 1.4% under B. pendula and P. sylvestris ), higher contribution of species typical for fertile forest edges (11.4 species vs. 5.9 species on average under B. pendula and P. sylvestris ) and lower number of species of the family Fabaceae (1.5 species vs. 5.2 species on average under B. pendula and P. sylvestris ). Effects of P. sylvestris stands depended on soil texture. On soils with more than 15% of silt and clay, generally, no effects were observed. However, on sandy soils (more than 85% of sand) we reported lower soil reaction (pH 6.3 in aqueous solution vs. 7.3 under B. pendula ) and smaller number of plant species (17 vs. 28 on average under B. pendula ). Our results showed that the tree species used for afforestation significantly influenced the characteristics of the forest ecosystems, even more than abiotic conditions.